THE CONSTRUCTION OF ACADEMIC OPTIMISM SCALE (AOS) TO DESCRIBE OPTIMISM IN EDUCATIONAL SETTING - Alim, Syahrul; Rakhmat, H. Andi Budhi (Lembaga Penelitian dan Pengabdian pada Masyarakat Universitas Bosowa, 2020)
Optimism is a cognitive construct that relate to individual efforts to get their goals. In the education context, optimism is positively correlated with performance and academic achievement. Optimistic individuals show good motivation and successfull completed their education on time. The study is aimed to understand academic optimism of student. Good understanding on it will be a usefull information to the university. This study uses quantitative method with N 441. The first study involved n 113 and the last n 328 respondents. Data analysis using descriptive analysis with the JASP application. Psychometric property analysis is performed using CFA (Confirmatory Factor Analysis) and reliability analysis uses Cronbach Alpha. The results showed that the psychometrics property of the AOS (Academic Optimism Scale) was quite reliable with a reliability value of 0.891. Items loading factor above 0.30 while the total varian expalined 35%. Meanwhile, the descriptive analysis suggested academic optimism at Bosowa University students on the moderate level, which was 63% and only around 21% at a high level while the remaining 16% was in the low category. It means that students' academic optimism still needs to be improved through various approaches.